Values and vaccine refusal : hard questions in ethics, epistemology, and health care - Navin, Mark (Routledge, Taylor & Francis Group, 2016)
"In this first book-length philosophical treatment of vaccine refusal, Mark Navin argues that we can best understand current debates by placing them in a broader narrative about medical expertise and civic engagement. Values and Vaccine Refusal focuses on the shifting epistemic and moral terrain surrounding an educated public's relationship with healthcare and society--a relationship characterized by a wariness of experts and elites, a withdrawal from participation in public projects, and a do-it-yourself model of reasoning and practice. This is a must-read for students and researchers interested in public health, social epistemology, and the ethical dimensions of both"--